Pitfalls in the Use of Voxel-Based Morphometry as a Biomarker: Examples from Huntington Disease - Henley, S.M.D.; Ridgway, G.R.; Scahill, R.I.; Klöppel, S.; Tabrizi, S.J.; Fox, N.C.; Kassubek, J.; for the EHDN Imaging Working Group (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: VBM is increasingly used in the study of neurodegeneration, and recently there has been interest in its potential as a biomarker. However, although it is largely “automated,” VBM is rarely implemented consistently across studies, and changing user-specified options can alter the results in a way similar to the very biologic differences under investigation. MATERIALS AND METHODS: This work uses data from patients with HD to demonstrate the effects of several user-specified VBM parameters and analyses: type and level of statistical correction, modulation, smoothing kernel size, adjustment for brain size, subgroup analysis, and software version. RESULTS: The results demonstrate that changing these options can alter results in a way similar to the biologic differences under investigation. CONCLUSIONS: If VBM is to be useful clinically or considered for use as a biomarker, there is a need for greater recognition of these issues and more uniformity in its application for the method to be both reproducible and valid. CAGcytosine adenine guanineDARTELDiffeomorphic Anatomical Registration Through Exponentiated Lie algebraEHDNEuropean Huntington' Disease NetworkFDRfalse discovery rateFWEfamily-wise errorFWHMfull width at half-maximumGMgray matterHDHuntington diseaseMod.modulationNAnot applicableSPMstatistical parametric mapping/statistical parametric mapTFCtotal functional capacityTIVtotal intracranial volumeUHDRSUnified Huntington Disease Rating ScaleUncor.uncorrectedVBMvoxel-based morphometry